Assessing long‐term maintenance of staff performance following behavior skills training in a home‐based setting. (14th August 2018) - Aherne, Christine M.; Beaulieu, Lauren
Abstract : We used a multiple baseline across participant design to evaluate the effects of behavior skills training on teaching three behavior therapists to implement discrete trial teaching (DTT) and evaluate the long‐term maintenance of skills acquired through behavioral skills training. For participants whose skills did not maintain, the authors evaluated an independent self‐evaluation procedure on their performance. Following DTT implementation training, maintenance probes were assessed at 2‐, 4‐, 6‐, and 8‐week follow‐ups. The results demonstrated that one participant maintained 100% procedural integrity (PI) through all follow‐ups, one participant decreased below mastery criterion at the 2‐week follow‐up, and one participant dropped below mastery criterion at the 4‐week follow‐up. Those participants that demonstrated decreased accuracy of implementation of DTT programs and were taught to implement a self‐evaluation procedure. Following self‐evaluation, PI maintained for up to 7 weeks for one participant. Our results suggest that if PI does not maintain, self‐evaluation may be a supplementary intervention to increase and maintain PI of new employees.